EFFECT OF ARCHITECTURAL TREE MODEL TO THE NOISE LEVEL OF MOTOR VEHICLE ON DEMANG LEBAR DAUN STREET PALEMBANG - Jumingan, Jumingan; Dahlan, Zulkifli; Setiabudidaya, Dedi (BIOVALENTIA: Biological Research Journal, 2016)
The research on the effect of architectural tree model to the noise level of motor vehicles on Demang Lebar Daun Street Palembang has been conducted. The purpose of this study was to analyze kind of architectural tree model can reduce the highest noise levels among the architectural tree models encountered and identify the architectural tree model. The method used was purposive sampling. Measurement of the noise level and architectural models were selected according to the type of the tree encountered on the left or right side of the street. The noise level measurement during the daylight was carried out simultaneously at a point of 1 meter in front of the tree, 1 and 5 meters behind the tree,for 10 minutes with the readings for every 5 seconds at 07:00, 10:00, 15:00 and 20:00. The results showed that The architectural model of Switenia magahoni tree was Rauh model, Lagerstroemia sp. tree was Troll model and Thyrsostachys siamensis tree was McClure model. The highest noise level reduction was from bamboo tree, respectively by 4,88 dB (A) and 8,52 dB (A) at the distances of 1 and 5 m.Â Keywords: noise level, reduction, architectural tree model